PENGARUH PROMOSI MELALUI APLIKASI ONLINE, PENGALAMAN KONSUMEN, VARIASI PRODUK, DAN KUALITAS PELAYANAN TERHADAP MINAT BELI KEMBALI PRODUK MIXUE YOGYAKARTA - Alfansia Daminta Kartika Patty; Daniel Joel Immanuel Kairupan (LPPM STIE YKPN Yogyakarta, 2022)
This research was conducted to examine the effect of promotions through online applications, consumer experience, product variety, and service quality on repurchase intentions in Mixue Yogyakarta. The selection of the sample in this study used a purposive sampling method with the criteria of the people of Yogyakarta who had made a purchase at Mixue. The data used is primary data. Data were taken directly by distributing online questionnaires via google form to respondents with a sample of 143 respondents. The results of this study indicate that promotion through online applications (X1), consumer experience (X2), and product variety (X3) have a positive and significant effect on repurchase intentions, while service quality (X4) has no effect on repurchase intentions.